Sleep Smarter: The Essential Guide To Sleep Hygiene Through Ayurveda (International Journal of Food and Nutritional Sciences, 2025)
Although research has demonstrated links between individual sleep hygiene components and subsequent sleep, evidence for the efficacy of sleep hygiene education as a treatment for insomnia has been limited and inconclusive. Sleep hygiene is defined as a set of behavioural and environmental recommendations intended to promote healthy sleep1. It was originally developed for use in the treatment of mild to moderate insomnia. During sleep hygiene education, patients learn about healthy sleep habits and are encouraged to follow a set of recommendations to improve their sleep (e.g., avoid caffeine, eliminate noise from the sleeping environment, maintain a regular sleep schedule)2-5.Sleep hygiene refers to the practices and habits that are necessary to have goodnight time sleep quality and full daytime alertness. Good sleep hygiene is crucial for maintaining both physical and mental health, enhancing productivity, and improving overall quality of life.